Early-onset status epilepticus in patients with acute encephalitis. Issue 30 (July 2016) - Sonneville, Romain; Mariotte, Eric; Neuville, Mathilde; Minaud, Sébastien; Magalhaes, Eric; Ruckly, Stéphane; Cantier, Marie; Voiriot, Guillaume; Radjou, Aguila; Smonig, Roland; Soubirou, Jean-François; Mourvillier, Bruno; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Status epilepticus (SE) is a common complication of acute encephalitis, but its determinants and prognostic value in this setting are not known. Risk factors for early-onset SE (within 48 hours of intensive care unit [ICU] admission) in consecutive adult patients with all-cause encephalitis admitted to the medical ICU of a university hospital (1991–2013) were evaluated by multivariate logistic regression analysis. To examine the prognostic value of SE, patients were classified into 3 groups: no SE, nonrefractory SE (NRSE), and refractory SE (RSE). Poor neurologic outcome was defined by a modified Rankin score of 4 to 6. Among the 290 patients, 58 (20%, 95% CI: 15%–25%) developed early-onset SE, comprising 44 patients with NRSE and 14 patients with RSE. Coma (adjusted odds ratio [OR]: 3.1, 95% CI: 1.5–6.3), cortical lesions on neuroimaging (adjusted OR: 3.7, 95% CI: 1.8–7.8), and nonneurologic organ failure(s) (adjusted OR: 13.6, 95% CI: 4.9–37.7) were found to be independent risk factors for SE. By contrast, a bacterial etiology had a protective effect (adjusted OR: 0.3, 95% CI: 0.1–0.7). Age, body temperature, and blood sodium levels were not independently associated with SE. Poor neurologic outcomes were observed at day 90 in respectively 23% (95% CI: 17%–28%), 23% (95% CI: 10%–35%), and 71% (95% CI: 48%–95%) of no SE, NRSE, and RSE patients ( P < 0.01). After adjusting for confounders, RSE, but not NRSE, remained independently associated with 90-day mortality (adjusted OR: 6.0, 95% CI: 1.5–23.3). Coma, cortical involvement on neuroimaging, and nonneurologic organ failure(s) are independent risk factors for SE in patients with acute encephalitis. Conversely, a bacterial etiology is associated with a lower risk of SE. These findings may help identify patients who may benefit from prophylactic antiepileptic drugs.